Waist-Hip Circumference Ratio as Strongest Factor Correlation with Blood Glucose Level - Mitha - Karimah (Jurnal Berkala Epidemiologi, 2018)
Background: In the present time, the prevalence of obesity in Indonesia continues to increase, especially in the pre- to the elderly citizen. It has been revealed that the citizen with age group 55-64 years have the highest risk to obtain obesity. Moreover, the insulin resistance that occurs in overweight groups suppresses the insulin activity which in turn increase the blood glucose levels. Purpose: This study aims to determine the relationship between waist-hip ratio and body mass index toward blood glucose levels. Methods: This study was cross-sectional design. The respondents were 36 elderly citizens aged between 46-70 years who were registered as members of the Posyandu (integrated health service station) Bunga Kasih for elderly health care. Random sampling technique was used in this study. Furthermore, the variables examined were body mass index, waist-hip ratio and fasting blood glucose levels. Data were analyzed using the Pearson correlation test with a significance level (α) = 0.05. Results: The majority of respondents included in the category of overweight-two were accounting about 36.10%, abdominal obesity based on waist-hip ratio accounting about 63.90% and blood glucose levels of more than 125 mg/dl by 25%. Pearson correlation test showed that the waist-hip ratio has a significant relationship with blood glucose levels with p <0.05 (p = 0.01; r = 0.49). However, there was no relationship between body mass index and blood glucose level with p> 0.05 (p = 0.32; r = 0.17). Conclusion: Waist-hip ratio has a strong relationship with blood glucose levels compared to body mass index.